Pengaruh Lingkungan Kerja Fisik dan Psikososial terhadap Kinerja SDM dalam Organisasi Berbasis Layanan di Puskesmas Bambu, Kabupaten Mamuju - Jusnaimah; Halim, Agus; Asia, Nur (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
Human resource performance in primary healthcare centers plays a critical role in ensuring the quality and effectiveness of public health services. However, employee performance is often influenced by the condition of both physical and psychosocial work environments. This study aimed to examine the effect of physical and psychosocial work environments on human resource performance at Puskesmas Bambu, Mamuju Regency. A quantitative approach with a survey design was applied, involving all employees through a census method. Data were collected using structured questionnaires with a Likert scale and analyzed using multiple linear regression after meeting classical assumption requirements. The findings reveal that both physical and psychosocial work environments have a positive and significant influence on employee performance, both simultaneously and partially. The psychosocial work environment demonstrates a more dominant contribution compared to the physical work environment. These results indicate that supportive workplace relationships, effective communication, and supervisory support significantly enhance employee motivation, responsibility, and service quality. It is concluded that improving work environment conditions, particularly psychosocial aspects, is essential for strengthening employee performance and healthcare service outcomes. Sustainable managerial strategies are recommended to foster a supportive and well-facilitated work environment.